Gestão do conhecimento na Ciência da Informação no Brasil: estruturas cognitiva e social no seu processo de institucionalização científica - Feitoza, Rayan Aramís de Brito (2022)
Knowledge Management has been highlighted as a theme of interest in different scientific fields, including Information Science. It analyzes the process of scientific institutionalization of Knowledge Management in Information Science in Brazil, from its social and cognitive structures. In relation to methodological procedure, it is characterized as an exploratory and descriptive research with quantitative and qualitative approach, of document and bibliographic type. It is performed two stages in the research operationalization: systematization of analytic categories, of indicators and components as evaluation criteria; and identification and description of structural components of scientific institutionalization. In the first stage, it is adopted Content Analysis in order to systematize the evaluation criteria of the current stage of social and cognitive institutionalization of Knowledge Management, based on Whitley theory. In the second stage, for the identification of components of the cognitive structure of Knowledge Management, it is elected as universe the works published on the annals of 21 editions of the National Meeting of Research in Information Science and the sample is consisted of the scientific production about Knowledge Management in the event, the most productive authors and the representatives of thematic nucleus defined by established criteria. Also, for the identification of components of the social structure of Knowledge Management, it is surveyed documents on the Sucupira Platform of the Coordination for the Improvement of Higher Education Personnel, on the Directory of Research Groups, and on the Lattes Curriculum of the Lattes Platform of the Brazilian National Council for Scientific and Technological Development, as well as on the sites of graduate programs in Information Science, of scientific journals, of the cooperation network and of scientific events. As analysis procedures, it is also used metric studies of information, starting from Bibliometrics, with quote analysis. It is identified linearity and terminological variation of the theme from the keywords and it is noted that the predominance of the most incident terms denotes the approaches of Knowledge Management and gives prevision of themes for future researches. The theoretical and methodological foundations that support the researches about the theme point the predictability of authors and titles of Knowledge Management, from the incidence of quotes done by the authors. Moreover, it is identified institutions that offer graduate programs and their respective research lines, research groups and cooperation network, determining that these spaces are formative units for people interested in the theme, as well as they enable the strengthening of the scientific community and internal social identity of Knowledge Management in this field. Specialized journals and scientific events about the theme are also identified, verifying the strengthening of the external social identity of Knowledge Management. It is identified the formative profile and the institutional affiliations of allocation of the responsible researchers by Knowledge Management. It is concluded by confirming the hypothesis and the thesis that Knowledge Management is found in process of evolution and maturity, with an elevate level of institutionalization in Information Science in Brazil, from its social and cognitive structures, positioning as a specialty with approaches which configure themselves as research areas.